2021
DOI: 10.1159/000519711
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Response 3 Months after 2 Doses of BNT162b2 mRNA COVID-19 Vaccine in Residents of Long-Term Care Facilities

Abstract: <b><i>Background:</i></b> Older adults living in long-term care facilities (LTCFs) are at increased risk for severe outcomes from COVID-19 and were identified as a priority group in COVID-19 vaccination strategies. Emerging evidence suggests vaccine effectiveness in LTCF populations, but data about median and long-term durability of immune response after vaccination are still limited. <b><i>Objectives:</i></b> In this study, we assessed the humoral response to BN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
12
1
Order By: Relevance
“…Another explanation for the detected differences between previous studies and the data presented here might be the age of the elderly population. Causa et al showed that the age-related decline of IgG titers has been particularly appreciable among individuals aged 80 or more (15). In their study, Muller et al (6) included aged people with a median age of 88 years (80.1-100.5 years), in contrast to our study, in which the average age was lower (70-94 years).…”
Section: Discussioncontrasting
confidence: 54%
“…Another explanation for the detected differences between previous studies and the data presented here might be the age of the elderly population. Causa et al showed that the age-related decline of IgG titers has been particularly appreciable among individuals aged 80 or more (15). In their study, Muller et al (6) included aged people with a median age of 88 years (80.1-100.5 years), in contrast to our study, in which the average age was lower (70-94 years).…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, in fully vaccinated older adults, there are no significant sex differences in antibody titers (Causa et al, 2021;Kontopoulou et al, 2021;Ríos et al, 2021). Among LTCFR who recovered from SARS-CoV-2 infection, however, there is a trend of higher antibody levels in females than males (Canaday et al, 2021).…”
Section: Sex Differences In the Response To Influenza Vaccination In ...mentioning
confidence: 94%
“…In the older adult cohort, receipt of a third vaccine dose largely eliminated disparities caused by sex, age, and frailty in antibody responses, with the exception of ACE2iAb, which remained lower in frail compared to non-frail or pre-frail participants. The effect of age on SARS-CoV-2 vaccine responses has been studied [7][8][9][29][30][31][32][33], but the sex differential impact of age has not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…In the older adult cohort, receipt of a third vaccine dose largely eliminated disparities caused by sex, age, and frailty in antibody responses, with the exception of ACE2iAb, which remained lower in frail compared to non-frail or pre-frail participants. The effect of age on SARS-CoV-2 vaccine responses has been studied [7-9, 29-33], but the sex differential impact of age has not been reported previously. Furthermore, studies investigating frailty have not found an effect on antibody responses [34-36], but have reported that frailty increases the risk of post-vaccination breakthrough infection [37, 38], suggesting that the immunogenicity studies may have been under-powered to observe an effect of frailty or that lack of consideration of biological sex obscured the effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation